La professionnalisation du développement durable : au-delà du clivage ou de la réconciliation écologie – économie - Nicole Huybens; Claude Villeneuve (VertigO)
Sustainable development is still today often confused with environmental protection for many stakeholders in industry as well as governments and the general public. For enviromentalists however it is not basically different from the business as usual approach with a green surfacing. An analysis of the concept’s history from its origin to the latest applications, reveals some caracteristics which require a real change of paradigm to qualify sustainability in the development.The sustainable development is rooted in actions at the local level with local stakeholders. We disagree with pessimists that consider sustainable development as a dead end or an oxymoron. Furthermore, there are ways and tools to implement sustainability at the project level as well as policy initiatives. The first are not formalized and the latest are seldom teached in a perspective of sustainable development. The paradigm of sustainable development needs to promote decisions and actions with a degree of complexity that largely overpass the cleavage or the simple reconciliation of economy and environment. We focus our contribution on the much needed training for sustainable development, allowing to better explain the existing tools and know-how, wishing them to initiate now the transformation of human development towards sustainability.